Pengkajian Pengamanan Bandara Frans Kaisepo-Biak - Rosidin Syamsudin (WARTA ARDHIA, 2009)
Air transportation services, security and flight safety is the main factor. Various efforts made to continually improve the level of security and safety of the flight, the good with the upgrade facilities, repair and operational management capacity building resources, human beings. International Civil Aviation Organization (ICAO) in Annex 17 Of the Security-Safeguarding International Civil Aviation Against Acts of Unlawful Interference requires that each number country is obliged to create a procedure and an action brought to prevent weapons or dangerous materials in civil aircraft.As explain standard of the above, then set the various systems and procedures of implementation in every airport and every company in the air transportation. The security of the flight center of gravity is related to passenger and goods that will leave / and transported aircraft.